Biochemical comparison of four commercially available human α1-proteinase inhibitors for treatment of α1-antitrypsin deficiency. (November 2017) - Boerema, David J.; An, Bo; Gandhi, Ronak P.; Papineau, Randy; Regnier, Ed; Wilder, Anna; Molitor, Alexander; Tang, Andrew P.; Kee, Scott M.
Abstract: Intravenous therapy with purified plasma-derived alpha1 -proteinase inhibitor (α1 -PI) concentrates is the only specific treatment for α1 -PI deficiency. For the therapy to be safe and efficacious, α1 -PI concentrates should be highly pure and contain high amounts of functional protein. This study compared the four plasma-derived α1 -PI products commercially available in Europe (Respreeza, Prolastin, Alfalastin, Trypsone) by biochemical methods with respect to function, purity, structure, and chemical modifications. Respreeza had the highest level of functional protein (48.8 mg/mL) and the highest specific activity (0.862 mg active α1 -PI per mg total protein). By size exclusion chromatography, Respreeza was 97.4% pure, followed by Alfalastin 88.1%, Prolastin 76.9%, and Trypsone 70.8%. By reversed phase chromatography, Respreeza had an α1 -PI purity of 97.7%, followed by Trypsone 88.0%, Prolastin 78.0%, and Alfalastin 69.5%. The main protein band by sodium dodecyl sulphate-polyacrylamide gel electrophoresis was found for all products at approximately 50 kDa. Additional protein bands were found for Prolastin, Alfalastin, and Trypsone. The α1 -PI products differed in cysteine oxidation state and C-terminal lysine status. α1 -PI products tested differ in purity, concentration, and chemical variation. Respreeza has the highest level of purity. The impact of the non-therapeutic proteins identified has not been evaluated.